The Development of Entrepreneurial Culture Among Students Through Innovation: Case of Sidi Mohamed Ben Abdellah University - Aicha EL Azzaoui (Iraqi Journal of Science, 2021)
Entrepreneurial culture has emerged as a powerful means of development in many countries of the world and can be regarded as a source of innovation and as a key to sustainable unemployment.The national economic outlook, which was established by the High Commission for Planning, predicts economic growth of only 2.6% in 2016, this growth will not provide sufficient employment.Morocco seeks to foster the entrepreneurial spirit of young Moroccans in order to encourage the creation, development of enterprises and the remuneration of investment in the service of employment through various policies that promote the " innovation.Students and university graduates (including students from Sidi Mohamed Ben Abdellah University in Fez) are the most involved social group. Through this research, we will try to describe the entrepreneurial culture of students through a field study.Our article is structured in the following way. In the first part, we try to treat the entrepreneurial culture by trying to take a general look, first of all, on its definition, then on the myths of entrepreneurship. In our second part, we talk about the entrepreneurial culture at the Sidi Mohamed Ben Abdellah University and the promotion of this culture among students through a field survey.Since 2011, the university has also initiated the program "innova project", whose mission is to organize training courses for business creation and innovation for the benefit of students from different institutions.